2016
DOI: 10.1155/2016/2168780
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Clinical Characteristics of Single and Multiple Respiratory Virus Infections Diagnosed in Croatian Children in Two Respiratory Seasons

Abstract: The aim of this study was to determine the causative agent of acute respiratory infection (ARI) in hospitalized children, as well as investigate the characteristics of ARIs with single and multiple virus detection in two respiratory seasons. In 2010 and 2015, nasopharyngeal and pharyngeal swabs from a total of 134 children, admitted to the hospital due to ARI, were tested using multiplex PCR. Viral etiology was established in 81.3% of the patients. Coinfection with two viruses was diagnosed in 27.6% of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
3
17
0
2
Order By: Relevance
“…Viral infections were confirmed in 58.5% and 33.9% of the males and females respectively with male to female ratio of 1.4:1. Similar ratio was reported by Ljubin-Sternak et al [41], who detected ARI in 109 out of 134 patients with a male to female ratio of 1.5: 1. Liu et al [42] examined 4,242 pediatric patients in southern China for respiratory viruses and reported even a higher male to female ratio of 1.92:1.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Viral infections were confirmed in 58.5% and 33.9% of the males and females respectively with male to female ratio of 1.4:1. Similar ratio was reported by Ljubin-Sternak et al [41], who detected ARI in 109 out of 134 patients with a male to female ratio of 1.5: 1. Liu et al [42] examined 4,242 pediatric patients in southern China for respiratory viruses and reported even a higher male to female ratio of 1.92:1.…”
Section: Discussionsupporting
confidence: 89%
“…Liu et al [42] also detected HCoVs in only 5.8% of their 2,361 cases. Similarly, Ljubin-Sternak et al [41] detected HCoVs in 4.2% of their cases.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The viruses most frequently detected are: influenza viruses A and B (IAV, IBV), human parainfluenza virus (HPIV), human adenovirus (HADV), human metapneumovirus (HMPV), and human respiratory syncytial virus (HRSV). This list is constantly evolving along with improvement in the performance of diagnostic tests (Ljubin-Sternak et al, 2016;Tregoning and Schwarze, 2010) and the discovery of more recent viruses, for example, human bocavirus (HBOV) (Allander et al, 2005), human coronaviruses (HCOVs) NL63 and HKU1, and new human enterovirus (HEV), parechovirus, and rhinovirus strains (Berry et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported co-detection rates of respiratory viruses ranging from 7 to 40 % [18,35,37]. Co-detection was observed in the form of influenza-CMV and HMPV-CMV in 8.5 % of specimens especially in children under the age of 6 years, none of which were associated with severe clinical manifestations.…”
mentioning
confidence: 99%